Background To effectively plan for human resources for health, health managers need to keep track of the size and composition of their human resources and to anticipate their future needs. Effective strategic planning is however informed by quality and re: Examining Challenges Affecting Management of Health Workers’ Information in Uganda - Mpiima, Jamiru; Nabukenya, Josephine (Journal of Health Informatics in Africa, 2019)
BackgroundTo effectively plan for human resources for health, health managers need to keep track of the size and composition of their human resources and to anticipate their future needs. Effective strategic planning is however informed by quality and reliable workforce information. However, in Uganda, existence and access to adequate information on human resources for health still remains a challenge. This limits the capacity of health managers to effectively monitor and make policies. To this end, this study set out to examine the challenges that affect the management of health human resources information in Uganda; with an aim to recommend a single authoritative source of health workforce information that can provide an accurate count of all health work-force in Uganda’s health system.MethodsWe used qualitative methods to examine the challenges that are affecting the management of health workers information in Uganda. Key informant interviews were conducted with purposively selected health-related organizations with a stake in human resources for health information management.Results The study reports various systems used for health workforce information management, the common one being the integrated Human Resources Information System (iHRIS). The study also provides various challenges affecting these systems including fragmentation and uncoordinated human-resource systems, which results to duplication of health workers records, incomplete or missing data elements, and inaccurate health workforce accountability.  Conclusion Given the nature of the challenges, the study denotes the need for a single authoritative source of health workforce information that can provide an accurate count of all health workforces in Uganda’s health system commonly known as a National Health Worker Registry. The registry can be used to aggregate the key attributes for all health workers in the country. Thus our future study will focus on defining country-specific features and requirements that NHWR should poses.